2014
DOI: 10.1007/s11262-014-1072-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel quasi-subgenotype D2 of hepatitis B virus identified in Taiwanese aborigines

Abstract: The hepatitis B virus (HBV) genomes in Taiwanese aborigines, whose ancestors have lived in Taiwan for over 10,000 years, have not been characterized. In order to characterize of HBV in this special population, serum samples were obtained from serologically HBsAg-positive 27 Taiwanese aborigines. The pre-S1/S2 region and the full-length 3.2 kb of the HBV genome were amplified by PCR. Obtained amplicons were sequenced and confirmed the HBV genotypes by phylogenetic analysis. By phylogenetic analysis of the seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…In the present work, eight isolates belonging to HBV/D (S18014, S140014, S20014, S140914, S02E12, S2312E, S07E, and S10612E) segregated with sub-genotype D1 reference isolates, and the inter distances equaling 0.006 verified this effect. This result is in agreement with recent studies that reported the prevalence of HBV/D1 in regions of the Middle East through North Africa (EL Hadad et al, 2013, Tran et al, 2014). Additionally, a possible new HBV sub-genotype (DA) was suggested by 3 isolates, S028, S318S, and S118S, which showed identity similarities of 94−96%.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present work, eight isolates belonging to HBV/D (S18014, S140014, S20014, S140914, S02E12, S2312E, S07E, and S10612E) segregated with sub-genotype D1 reference isolates, and the inter distances equaling 0.006 verified this effect. This result is in agreement with recent studies that reported the prevalence of HBV/D1 in regions of the Middle East through North Africa (EL Hadad et al, 2013, Tran et al, 2014). Additionally, a possible new HBV sub-genotype (DA) was suggested by 3 isolates, S028, S318S, and S118S, which showed identity similarities of 94−96%.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, ten sub-genotypes of HBV/D (D1 to D10) have been reported, each showing distinct geographical clustering (Tran et al, 2014). In the present work, eight isolates belonging to HBV/D (S18014, S140014, S20014, S140914, S02E12, S2312E, S07E, and S10612E) segregated with sub-genotype D1 reference isolates, and the inter distances equaling 0.006 verified this effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, eight isolates belonging to HBV/D (S18014, S140014, S20014, S140914, S02E12, S2312E, S07E and S10612E) are segregated with subgenotypes D1 reference isolates and inter distance equal 0.006 that was verified this result. Those in agreement with, recent studies reported the prevalence of HBV/D1 in regions of the Middle East through North Africa (Tran et al, 2014;El Hadad et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, ten subgenotypes of HBV/D (D1 to D10) have been reported, each subgenotype showed distinct geographical clustering (Tran et al, 2014). Because little is known about the prevalence, distribution and sequences of HBV subgenotypes in Saudi Arabia, particularly Jeddah, no previous data was available (Al-Faleh et al, 1992.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Therefore, it is not surprising that several research efforts in the last decade have been directed to discover the different HBV sub-genotyping in several countries. [8][9][10][11] During HBV replication, the lack of proofreading ability of the reverse transcriptase leads to an error rate that is 10-fold higher than Mohammed El-Mowafy and Abdelaziz Elgaml contributed equally in this work.…”
mentioning
confidence: 99%